Можливості застосування адсорбційного методу для визначення товщини наноблоків у терморозширеному графіті - Nasiedkin, D. B.; Babich, I. V.; Plyuto, Yu. V. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2010)
The adsorption method was applied to determine the platelets thickness in expanded graphite (EG) and the number of graphene sheets which compose them. A platelets thickness in the synthesized samples of EG was found to be of 18-36 nm what corresponds to 50-100 graphene sheets. The application of the square-shaped and the round-shaped model of basal graphene plane give similar results. The results obtained with the applied models of the platelet structure were confirmed with results of graphene platelets examination by X-Ray difractometry